2018
DOI: 10.1785/0120170195
|View full text |Cite
|
Sign up to set email alerts
|

Constraints of Crustal Heterogeneity and Q(f) from Regional (<4  Hz) Wave Propagation for the 2009 North Korea Nuclear Test

Abstract: We carried out 3D finite‐difference (FD) simulations (<4  Hz) of regional wave propagation for the 2009 North Korea nuclear explosion and compared the synthetics with instrument‐corrected records at stations INCN and TJN in South Korea. The source is an isotropic explosion with a moment magnitude of 4.1. Synthetics computed in the relatively smooth Sandia/Los Alamos National Laboratory SALSA3D (SAndia LoS Alamos 3D) velocity model significantly overpredict Rayleigh‐wave amplitudes by more than an order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our interpretation is that with increasing distance, more or greater velocity contrasts along a ray's path yields more energy lost to scattering (refractions or reflections), and less energy transmitted. Recent numerical modeling studies (Olsen et al, 2018) have found similar results. At closer distances, we observe a weak positive correlation between path residuals and dVI, which is perhaps unsurprising.…”
Section: 1029/2018jb016796supporting
confidence: 69%
“…Our interpretation is that with increasing distance, more or greater velocity contrasts along a ray's path yields more energy lost to scattering (refractions or reflections), and less energy transmitted. Recent numerical modeling studies (Olsen et al, 2018) have found similar results. At closer distances, we observe a weak positive correlation between path residuals and dVI, which is perhaps unsurprising.…”
Section: 1029/2018jb016796supporting
confidence: 69%
“…In recent years, significant progress has been made in modeling synthetic ground motions. With the advance of modern computing power, studies such as Bydlon et al (), Graves and Pitarka (), Mai et al (), Taborda et al (), Imperatori and Mai (), Frankel et al (), Wirth et al (), Withers, Olsen, Day, and Shi,(), Withers, Olsen, Shi, and Day, (), Olsen et al (), Graves and Pitarka (), Andrews and Ma (), Hartzell et al (), Pitarka et al (), Pitarka et al (), and Moschetti et al () have incorporated increasingly accurate physics into simulations. Some of these improvements include explicitly accounting for complex rupture processes and the propagation of waves through realistic 3‐D crustal structure to simulate ground motions at a wider range of frequencies for a variety of end‐use cases (from assessing regional seismic hazard related to basin amplification to better understanding the role of anelasticity in nuclear monitoring).…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of that approach are daunting, as indicated for example, by K. B. Olsen et al (2018) in their finite difference simulations of regional seismic waves at stations in the Republic of Korea (South Korea) from the DPRK nuclear test of 2009.…”
Section: Locations Based On Phase Picks For Each Seismic Event Contra...mentioning
confidence: 99%
“…B. Olsen et al (2018) pushed simulation of wave propagation in state-of-the-art 3D crustal models, using a fairly smooth 3D model with 24 billion points at uniform spacing (100 m), noting that modern capabilities enable synthetics up to 4 Hz out to distances of several hundred km. They included anelastic attention parameterized by a variety of Q models, and achieved some success with synthetics that matched the timing of observed regional wave arrivals; but they at first grossly overpredicted Rayleigh-wave amplitudes and under-predicted the coda.…”
Section: Locations Based On Phase Picks For Each Seismic Event Contra...mentioning
confidence: 99%